Implementasi Model Pembelajaran Advance Organizer Berbasis Peta Konsep Terhadap Aktivitas Belajar Dan Hasil Belajar Siswa - Yogi Sudrajat; Sulistyono Sulistyono; Anna Fitri Hindriana (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
This research is motivated by students' science process skills that are still low. Factors that cause low science process skills are low mastery of students' concepts of subject matter. The purpose of this study is 1) to describe the implementation of learning with the implementation of an advance organizer model based on concept maps on learning activities and student learning outcomes, 2) to determine the implementation of the advance organizer model based on concept maps can improve student learning activities, 3) to determine the implementation of the model advance organizer based on concept maps can improve student learning outcomes on the concept of the reproductive system, 4) to find out the response of the students to the implementation of the advance organizer model based on concept maps of learning activities and student learning outcomes. The method used in this study is mixed methods research. The sampling technique is cluster random sampling in two classes, namely the experimental class and 40 students for the control class. The research instrument used is the student activity task and rubric, concept mastery essay test, student response questionnaire on learning and teacher and student activity observation sheets. Data analysis techniques used are normality test, homogeneity test and hypothesis test. Based on the results of hypothesis testing statistics shows the value of Sig. amounting to 0.415 0.05, with a value of t = 4.855 with Sig. 0,000 0,05 means that the implementation of the advance organizer model based on concept maps can improve student learning activities on the concept of the reproductive system in class XI of SMA Negeri 1 Lumbung, Ciamis Regency. Based on the results of hypothesis testing statistics shows the value of Sig. amounting to 0.422 0.05, with a value of t = 8.336 with Sig. 0,000 0,05 means that the implementation of the advance organizer model based on concept maps can improve student learning outcomes in the concept of the reproductive system in class XI of SMA 1 Lumbung, Ciamis Regency. The conclusion in this study is the implementation of an advance organizer model based on concept maps can improve student activity and learning outcomes on the concept of reproductive systems in class XI of SMA Negeri 1 Lumbung, Ciamis RegencyKeywords: Advance organizer model; Concept map; Activity and student learning outcomes